The use of salicylaldehyde derivatives as a nitrogen source for antibiotic production by Streptomyces hygroscopicus CH-7 - Konstantinović, Sandra S.; Zlatković, Milica Z.; Ćirić, Jovan T.; Ilić, Slavica B.; Gojgić Cvijović, Gordana D.; Veljković, Vlada B. (HEMIJSKA INDUSTRIJA (Chemical Industry), 2018)
In the present work, four derivatives of salicylaldehyde (salicylaldehyde-hydrazone, phenylhydrazone, semicarbazone and thiosemicarbazone) were synthesized using both conventional (95% ethanol) and green (crude glycerol from biodiesel production) solvents. The obtained compounds were identified by elemental microanalysis, as well as FTIR, UV/VIS, 1H NMR and X-ray spectroscopic methods. Yields of 93-98% of the compounds in crude glycerol were achieved within 10-25 min. The derivatives of salicylaldehyde and crude glycerol were used as a nitrogen and carbon source, respectively, in the medium for antibiotic (Hexaene H-85 and Azalomycine B) production by Streptomyces hygroscopicus CH-7. The highest concentrations of Hexaene H-85 and Azalomycine B were achieved in the medium containing salicylaldehyde-thiosemicarbazone (198 g/cm3 and 69 µg/cm3, respectively). Derivatives of salicylaldehyde also impacted the strain morphology. In the media with salicylaldehyde-phenylhydrazone and salicylaldehyde-thiosemicarbazone, S. hygroscopicus CH-7 grew like large dispersive pellets with long twisted filaments that produced the highest yield of the antibiotics.